Human Factors Analysis on Creating an Inclusive Aircraft Lavatory Environment for Blind and Visually Impaired People - Kimberly Dippel (2012)
Despite blindness or visual impairment, people cannot or do not want to give up on traveling by plane. Since an airplane is not an everyday living space, it is particularly difficult for the blind and visually impaired to orientate themselves inside the aircraft cabin and the aircraft lavatory. Nowadays, the design and technologies inside the aircraft lavatory do not fit the needs of blind and visually impaired people. In order to make traveling by plane as pleasant as possible for blind and visually impaired people, they need to get best possible support by the cabin crew and through appropriate cabin design. The focus of this thesis is the derivation of requirements for an inclusive aircraft lavatory based on the needs of blind and visually impaired people as well as the application of these requirements on the development of a design concept of an aircraft lavatory.